The metric tide : lterature review : supplementary report I to the Independent Review of the Role of Metrics in Research Assessment and Management /: lterature review : supplementary report I to the Independent Review of the Role of Metrics in Research Assessment and Management. (July 2015) - Wouters, Paul, 1951-
No abstract available